Hydrogen Energy Technologies - Shabani, Bahman; Suryawanshi, Mahesh (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Hydrogen provides a promising technological solution for storing and delivering energy with minimal to no greenhouse gas emissions. It complements other energy storage options, such as batteries. Consequently, the global hydrogen industry is experiencing rapid growth to support the ambitious emission reduction targets set by countries worldwide. In tandem with this industry's growth, the research and innovation landscape in the hydrogen sector is evolving at a swift pace. These advancements are integral to fortifying the nascent hydrogen industry and its associated market. The hydrogen value chain encompasses multiple facets, including hydrogen production, transportation, storage, distribution, and utilization. Sustainability is paramount across all these dimensions, playing a pivotal role in seamlessly integrating hydrogen into our energy matrix as a viable and value-adding alternative. This reprint contains scientific papers that present recent studies covering various aspects of hydrogen technology, offering insights into different components of its value chain, touching on topics related to hydrogen economy, laws and policies, electrolysis, biohydrogen production, liquid hydrogen and solid-state hydrogen storage. Additionally, these studies explore various types of fuel cells, ranging from solid oxide and direct methanol cells to airborne fuel cells and PEM cells. These studies also touch upon catalysts, the utilization of waste heat from fuel cells, water recovery processes and the establishment of hydrogen fueling stations, among other critical topics.